THE IMPORTANCE OF ANOMALY SCREENING AND INVOLVEMENT OF MODERN TECHNOLOGIES IN DIAGNOSIS OF GENETIC ABNORMALITIES - Singh , S; Abdurazakova, M.D. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Recent advancements in technology have revolutionized prenatal screening and diagnostic methods for fetal genetic conditions. More recently introduced technologies such as chromosomal microarray analysis and whole-exome sequencing can diagnose more genetic conditions on samples obtained through amniocentesis or chorionic villus sampling, including many disorders that cannot be screened for non-invasively. All of these options have benefits and limitations, and genetic counseling has become increasingly complex for providers who are responsible for guiding patients in their decisions about screening and testing before and during pregnancy.